2014
DOI: 10.4103/0973-1482.131366
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological, immunohistochemical factors and recurrence associated with extrathyroidal extension in papillary thyroid microcarcinoma

Abstract: ETE of conventional PTMC is associated with size, multifocality, lymph node metastasis, and recurrence. More extensive surgery should be considered for patients having ETE identified by intraoperative frozen sections, preoperative imaging, and intraoperative finding and other high risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 45 publications
1
1
0
2
Order By: Relevance
“…A recent study on a large cohort of 1793 patients operated on for benign diseases discovered a 4.62% incidence of incidental PTMC [16]. As the percentage of incidental PTMC in our cohort was higher, our results agree with two other studies that reported that PTMC in histological specimens after thyroid surgery for benign diseases was found in 22% and 27.4% of cases, respectively [15,17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A recent study on a large cohort of 1793 patients operated on for benign diseases discovered a 4.62% incidence of incidental PTMC [16]. As the percentage of incidental PTMC in our cohort was higher, our results agree with two other studies that reported that PTMC in histological specimens after thyroid surgery for benign diseases was found in 22% and 27.4% of cases, respectively [15,17].…”
Section: Discussionsupporting
confidence: 91%
“…As evidenced by histopathological examination, a non-negligible percentage of PTMC may be aggressive [12]. The aggressiveness of PTMC is expressed by metastasis in both lymph nodes (LNs) and distant areas and by an increased recurrence rate, which can be similar to papillary cancer as a percentage [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…El compromiso ganglionar regional de los MCPT oscila entre el 14 y el 46 %, por lo que se debate el rol del vaciamiento central sistemático [15][16][17] . Tanto las guías ATA 2015, como otros autores, recomiendan realizar un vaciamiento ganglionar central solamente en tumores T3 y T4 18,19 , no obstante, algunos autores afirman que realizar vaciamiento ganglionar central sistemático en tumores T1 y T2 puede reducir la recurrencia locorregional del 4,5 -8,6 % hasta el 2,5 -5,9 % 20 .…”
Section: Introductionunclassified
“…Os dados estão nas tabelas 13 e 14 abaixo. A invasão tumoral extratireoideana ocorre em 7,5% até 31% dos casos de CDT (130)(131)(132) e é um fator de pior prognóstico bem estabelecido, sendo associado ao maior risco de recorrência e persistência tumorais, além de maior mortalidade (3,35). A relação entre maior tamanho corporal e a invasão do tumor para além da tireoide poderia ser explicada pela presença comum de marcadores específicos em ambas as situações.…”
Section: Análise Comparativa Dos Quartis De Asc E Evolução Do Tumorunclassified